Immobilization of fungal biomass with multi-walled carbon nanotubes as biosorbent - Murad, Fatin Nabilah; Ahmed Kabbashi, Nassereldeen; Alam, Md Zahangir; Alkatib, Ma’an Fahmi Rashid (Distributed & Published by: School of Industrial Technology Universiti Sains Malaysia, 2017)
An efficient and effective biosorbent with high performance is needed to remove impurities in solution and the conventional method of adsorption of fungal biomass alone not showing a promising removal of impurities. The immobilization of multiwalled carbon nanotubes (MWCNTs) with fungal biomass (A. niger) was good combination since both has potential functional group to bind to each other. This research was basically focused on combination of fungal biomass with MWCNTs to enhance the positive integration of impurities removal in solution. The immobilization of both elements was done in a batch liquid medium with several parameters like pH, agitation speed, dose of MWCNTs and inoculum dosage that were conducted with one factor at one time (OFAT) method. In order to verify the functional group of MWCNTs, A. niger biomass and immobilized A. niger biomass, the FTIR was applied and FESEM was done to demonstrate and compare the image of the immobilized A. niger biomass with MWCNTs and fungal biomass alone. The finding illustrated the best pH, agitation speed, dose of MWCNTs and inoculum dosage were 5-6, 150 rpm, 0.5 grams and 2% respectively. FTIR indicates the presents of the functional groups in before and after immobilization while FESEM showed the images of the wrapped MWCNTs on A.niger biomass.